2017
DOI: 10.1002/art.40147
|View full text |Cite
|
Sign up to set email alerts
|

Screening of 181 Patients With Antibody Deficiency for Deficiency of Adenosine Deaminase 2 Sheds New Light on the Disease in Adulthood

Abstract: Taken together, our findings indicate that DADA2 presents not only with vasculopathy but also with an immunodeficiency of the B cell compartment. Therefore, patients with antibody deficiency should be screened for DADA2. Anti-tumor necrosis factor treatment might improve immunologic features over time and might be considered in patients without vascular manifestations but with elevated inflammation markers. Conservative management has so far proven to be the choice for our less severely affected adolescent and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
110
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 113 publications
(122 citation statements)
references
References 23 publications
8
110
0
4
Order By: Relevance
“…Additionally, other disease manifestations such as laboratory abnormalities, individual growth and development, and esophageal varices secondary to portal hypertension improved on therapy . Schepp et al have also reported that suppression of inflammation resulted in restoration of B cell function in patients with mild immunodeficiency. However, the results have been less convincing for DADA2 patients presenting with severe cytopenia and/or immunodeficiency, some of whom failed the treatment and developed life‐threatening infection .…”
Section: Treatmentmentioning
confidence: 95%
See 3 more Smart Citations
“…Additionally, other disease manifestations such as laboratory abnormalities, individual growth and development, and esophageal varices secondary to portal hypertension improved on therapy . Schepp et al have also reported that suppression of inflammation resulted in restoration of B cell function in patients with mild immunodeficiency. However, the results have been less convincing for DADA2 patients presenting with severe cytopenia and/or immunodeficiency, some of whom failed the treatment and developed life‐threatening infection .…”
Section: Treatmentmentioning
confidence: 95%
“…From the first report on DADA2, features of mild immunodeficiency have been noted, with evidence for mild hypogammaglobulinemia and low IgM serum levels . Subsequently, an immunodeficient phenotype manifesting with recurrent sinopulmonary and herpes virus infections was reported in a subset of patients with DADA2 who were initially diagnosed with common variable immunodeficiency . Of reported patients, at least 25% had hypogammaglobulinemia, 10% had lymphopenia, and 10% had low switched memory B cells.…”
Section: Human Ada2 Deficiency: An Expanding Clinical Phenotypementioning
confidence: 99%
See 2 more Smart Citations
“…Since the time of the original description, there has been an expansion of the clinical phenotype of cases with DADA2, from cytopaenias and pure red cell aplasia [89], to lymphoproliferative disease [90–92], and combined immune deficiency, as well as common variable immune deficiency (CVID) [93]. Indeed, a cohort study of 181 cases with antibody deficiency diagnosed 11 individuals with mutation and enzyme activity confirmed DADA2 [94]. An interesting finding in this group was that anti-TNF therapy resulted in an improvement in IgM levels in one case, and there was an inverse correlation between c-reactive protein (CRP) and IgG in another.…”
Section: Classificationmentioning
confidence: 99%